FORMATION OF THE RELIGIOUS CHARACTER OF FEMALE ADOLESCENTS THROUGH FATAYAT NAHDLATUL ULAMA ACTIVITIES IN WONOKROMO VILLAGE, MOJOTENGAH, WONOSOBO - Eka Faena Guslaila; Sri Haryanto; Ali Imron (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2025)
Character education is one of the fundamental aspects in shaping the personality of the younger generation, especially amid the moral and spiritual challenges of the modern era. This study aims to determine: (1) the process of forming the religious character of adolescent girls through Fatayat Nahdlatul Ulama (NU), (2) the effectiveness of religious character formation through Fatayat NU activities in Wonokromo Village, Mojotengah District, Wonosobo Regency, and (3) the supporting and inhibiting factors in its implementation. This study employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving Fatayat NU administrators, members, adolescent girls, and the chairperson of Fatayat NU. Data analysis used the Miles and Huberman model, while data validity was ensured through source and method triangulation. The results show that the formation of religious character is carried out through routine religious studies, mujahadah, yasin and tahlil activities, and Friday charity programs. These activities contribute to the development of religious values, discipline, responsibility, social awareness, and Islamic morals among adolescent girls. Supporting factors include organizational support, family and community involvement, religious environments, and participants’ motivation. Meanwhile, inhibiting factors include limited participation, technological influences, time constraints, inadequate facilities, and differences in participants’ backgrounds. Therefore, Fatayat NU plays an important role in fostering the religious character of adolescent girls through continuous religious, social, and educational activities